Williamson on knowledge - Greenough, Patrick; Pritchard, Duncan; Williamson, Timothy (Oxford : Oxford University Press, 2009)
16 leading philosophers offer critical assessments of Timothy Williamson's ground-breaking work on knowledge and its impact on philosophy today. They discuss epistemological issues concerning evidence, defeasibility, scepticism, testimony, assertion, and perception, and debate Williamson's claim that knowledge is a mental state.
Description based on print version record.
Keywords: Williamson, Timothy; Knowledge, Theory of